MEASUREMENT OF THE HEAVY-ION COLLISION EVENT CHARACTERISTICS WITH THE ATLAS EXPERIMENT AT THE LHC - Grabowska-Bołd, Iwona; Burka, Klaudia; Bołd, Tomasz (Computer Science, 2015)
Heavy-ion collisions at extreme energies can reproduce conditionspresent in the early Universe. The new state of very dense and hotmatter of deconfined quarks and gluons, called the Quark GluonPlasma~(QGP), is observed. This state is characterised by very lowviscosity resembling the properties of a perfect fluid. In suchmedium, the density fluctuations can be easily spread. In experimentalpractice, the size of these fluctuations is estimated by measuring theangular correlation of produced particles. The aim of this paper isto present measurements of the azimuthal anisotropy of chargedparticles produced in heavy-ion collisions using the ATLAS detector atthe LHC. Two measurement techniques are presented and compared.